The demographic history of Palestine during the British administration (1917-1948) based on the official records of Palestine demography - Mohd Roslan Mohd Nor; Ummu Zainab Al-Abidah Zainal Abidin; Ezad Azraai Jamsari (Penerbit Universiti Kebangsaan Malaysia, 2015)
One of the physical transformations during the time of British Administration of Palestine occurred demographically, as a land that was once inhabited by a majority of Arabs was completely transferred into a Jewish dominated region in the space of only three decades and which had made possible the formation of the state of Israel. This paper will discuss different official records that provide information on the population of Palestine during the British Mandate and several matters pertaining to the sources of the selected data. This article will mostly be expository and focused on the historical records, while the related events warranted a more lengthy discussion and thus is beyond its scope. The method applied in this study is the historical method. The findings highlight some of the issues that exist within the scope of Palestine demographic study, particularly from the historical perspective.